BANK CUSTOMER PROTECTION BASED ON HIGH-LEVEL PRINCIPLE ASPECT ON FINANCIAL CONSUMER PROTECTION (G20 PARIS 2011) - Ahmad Fajar Herlani (Universitas Islam Negeri Mataram, 2020)
This writing discusses the protection of customers who experience delays and errors in electronic funds transfers caused by damage or interference from the bank. In this case, the bank experiences an inability to provide data access (availability of data) which should have been accessed by the customer for 24 hours. In providing access to customer protection data, it covers two aspects that must be considered, namely if the failure of the transfer occurs when the customer has not made an acceptance of the transfer (experiencing non-availability of data), then the customer has the right to complain to the bank. But if the transfer failure occurs when the customer has made an acceptance caused by natural disasters, danger, riots, armed conflicts, and/or other emergencies determined by the government that occurs in the area or location of the Original Sending Operator that is carrying out fund transfer orders, damage to electronic or non-electronic infrastructure systems that directly affect the implementation of Fund Transfer Orders that cannot be controlled by the Originator, the failure of the clearing system or the Fund Transfer System. Then the original sender is responsible to the original sender.